PENERAPAN AUDIT MANAJEMEN REKRUTMEN DAN KEPUASAN KERJA SDM WARUNG SEMBAKO MADURA RESTU BUNDA SUKOHARJO - Nany, Magdalena; Sari, Riski Nadila; Kurnia Sari, Lintang Ayu; Subroto, Asto Sunu (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2025)
Madura Restu Bunda Grocery Shop (WSMRB) competes closely with several similar stores around the University of Muhammadiyah Surakarta campus. The type of merchandise that is similar to competitors causes competition to shift to service that is closely related to the store's human resources. WSMRB has never conducted a human resource management audit. The data collection techniques used are interviews and observations. Meanwhile, the analysis of management audit elements used identifies conditions, criteria, causes and consequences. Stores should start planning and managing the recruitment process in a more professional, transparent, and structured manner, based on fair and transparent principles, which take into account the qualifications and abilities of potential employees, not just social relationships or personal networks.  With specific and measurable job satisfaction indicators, stores can be more effective in identifying problems, planning improvements, and creating a a positive work environment that can increase employee productivity and retention.